An Exploratory Study on Children’s Awareness Regarding Children’s Rights: Focusing on Their Understanding of the Right to Bodily Safety - Weerasinghe, Dhanushka Nuwan (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 3 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2024)
Child rights are essential for safeguarding the welfare and preservation of children; however, the extent to which children are aware of these rights is frequently disregarded. A mixed-methods approach was used to gather data from a mixed group of 100 school students aged 15 to 16 years. The collection of quantitative data involved the administration of structured surveys. In contrast, qualitative insights were acquired via focus group discussions and interviews to assess participants’ comprehension of diverse facets of child rights, especially bodily safety healthcare, education, protection against abuse, and participation. According to the study, 72% of the participants exhibited a rudimentary comprehension of their rights, whereas 20% displayed a restricted level of awareness. A total of 8% of the participants lack any knowledge regarding juvenile rights. Preliminary analysis indicates that participants possess differing degrees of awareness. Although confident children comprehensively comprehend fundamental rights like healthcare, education, and protection against violence, others display limited awareness, specifically about more intricate rights like freedom of expression and participation in decision-making. Age, gender, socioeconomic status, educational background, and parental educational levels were analysed to identify significant correlations with awareness levels. Furthermore, the research investigated the information sources about child rights and the obstacles children face in obtaining such data. The results underscore the significance of implementing focused educational interventions to improve children’s understanding of their rights. These interventions can enable children to assert their rights, foster an environment that values and respects the rights of children, and ultimately result in more equitable and inclusive societies. Furthermore, the research offers valuable perspectives on the efficacy of educational endeavours concerning children’s rights and sheds light on potential avenues for enhancing consciousness among students in academic institutions. Ultimately, this contributes to the empowerment and safeguarding of children’s rights.